THE WAY OF ORGANIZING THE FLOW OF AIRCRAFT BY INVERSE "TROMBONE" TYPE LOCATION OF THE USEFUL MANOEUVRING AREA - G. N. Lebedev; V. B. Malygin (Научный вестник МГТУ ГА, 2016)
The problem of solving important practical tasks of organizing the flow of arriving aircraft from different directions to the same navigation point is described. This allows us to form list for landing and determine their priority.